EDUKASI PEMANFA’ATAN INTERNET SEBAGAI SARANA PENDIDIKAN DAN DAKWAH DI KELURAHAN TAMAN AGUNG KECAMATAN BATHIN III KABUPATEN BUNGO PROVINSI JAMBI - Apdoludin Ludin Syamsuar; Radinal Fadli; Muhammad Hakiki; Yogi Irdes Putra; Ahmad Ridoh; Fauziah Fauziah (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
The rapid progress of information technology can no longer be stopped, one of its forms is the internet. The internet has an extraordinary magnet in human life, able to attract people in the suburbs to big cities, from young people to old people who cannot be separated from its magnetic pull. Internet users by the community need to get deeper supervision and direction so that the internet can be used as a means of education and da'wah, so that the use of the internet becomes a form of task fulfillment activity that is more focused and positive productive. Therefore, community service activities in Taman Agung, Bathin III , Bungo, Jambi Province are considered important. The activity is carried out in the following stages: 1) preparation of the required documents, 2) establishing friendship with the community, 3) introducing the concept of internet use to the community, and 4) lecturing, discussion and question and answer. The results of this activity are as follows: 1) the required documents are completed according to plan, 2) the community welcomes the arrival of the team, 3) the community is very enthusiastic in receiving an explanation of the concept of internet use from the presenters, 4) the community gets knowledge about the users Atan internet as a means of education and preaching and the community is very satisfied and wants this activity to be held sustainably. Keywords: Utilization, Internet, Education, Da'wah.